Incidence of adverse events in minimally invasive vs open radical hysterectomy in early cervical cancer: results of a randomized controlled trial - Obermair, Andreas; Asher, Rebecca; Pareja, Rene; Frumovitz, Michael; Lopez, Aldo; Moretti-Marques, Renato; Rendon, Gabriel; Ribeiro, Reitan; Tsunoda, Audrey; Behan, Vanessa; Buda, Alessandro; Bernadini, Marcus Q.; et al. (American journal of obstetrics and gynecology, 2020)
Standard treatment of early cervical cancer involves a radical hysterectomy and retroperitoneal lymph node dissection. The existing evidence on the incidence of adverse events after minimally invasive vs open radical hysterectomy for early cervical cancer is either nonrandomized or retrospective. The purpose of this study was to compare the incidence of adverse events after minimally invasive vs open radical hysterectomy for early cervical cancer. The Laparoscopic Approach to Carcinoma of the Cervix trial was a multinational, randomized noninferiority trial that was conducted between 2008 and 2017, in which surgeons from 33 tertiary gynecologic cancer centers in 24 countries randomly assigned 631 women with International Federation of Gynecology and Obstetrics 2009 stage IA1 with lymph-vascular invasion to IB1 cervical cancer to undergo minimally invasive (n = 319) or open radical hysterectomy (n = 312). The Laparoscopic Approach to Carcinoma of the Cervix trial was suspended for enrolment in September 2017 because of an increased risk of recurrence and death in the minimally invasive surgery group. Here we report on a secondary outcome measure: the incidence of intra- and postoperative adverse events within 6 months after surgery. Of 631 randomly assigned patients, 536 (85%; mean age, 46.0 years) met inclusion criteria for this analysis; 279 (52%) underwent minimally invasive radical hysterectomy, and 257 (48%) underwent open radical hysterectomy. Of those, 300 (56%), 91 (16.9%), and 69 (12.8%) experienced at least 1 grade ≥2 or ≥3 or a serious adverse event, respectively. The incidence of intraoperative grade ≥2 adverse events was 12% (34/279 patients) in the minimally invasive group vs 10% (26/257) in the open group (difference, 2.1%; 95% confidence interval, –3.3 to 7.4%; P=.45). The overall incidence of postoperative grade ≥2 adverse events was 54% (152/279 patients) in the minimally invasive group vs 48% (124/257) in the open group (difference, 6.2%; 95% confidence interval, –2.2 to 14.7%; P=.14). For early cervical cancer, the use of minimally invasive compared with open radical hysterectomy resulted in a similar overall incidence of intraoperative or postoperative adverse events.